Pharmacists’ Perceived Barriers to Patient Counseling - Abdulkareem M. Albekairy (Journal of Applied Pharmaceutical Science, 2014)
The aim of this study was to investigate the prevalence and nature of patient counseling barriers as perceived by pharmacists. The data was collected by adding a question about the existence and nature of counseling barriers, if they exist, to the standard patient counseling form used by pharmacists. The prevalence of counseling barriers was 12.5%. The major counseling barrier was counseling the caregiver instead of the patient (27.8%), followed by low level of education, lack of privacy, lack of interest/time and partial consciousness of the patient (16.7% each) and hearing impairment (11.1%). Finally gender and delay of discharge order were the least reported (5.26% each). This study recommends that a special counseling protocol should be implemented for patients with low level of education and partial hearing impairment and that a proper setting for counseling and strict implementation of policies should be provided by the institution.
Keywords: Patient Counseling, Discharge Counseling, Counseling Barriers, Pharmacy Practice.